Убийство Роджера Экройда: перевод с английского - Кристи Агата (1992)
Экземпляры: ф.13 (1992) / Инвентарный номер: 35994 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: К 82 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44